2011
DOI: 10.3144/expresspolymlett.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Permeability characterization of stitched carbon fiber preforms by fiber optic sensors

Abstract: Abstract. The in-plane and through thickness permeability of unidirectional stitched carbon fiber preforms have been determined through vacuum infusion tests. The impregnation of various dry preforms with different stitching characteristics has been monitored by fiber optic sensors that have been stitched together with the dry tow to manufacture the dry preform. The experimental infusion times have been fitted by a numerical procedure based on Finite Element (FE) processing simulations. A good agreement betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…During numerous research works, influences on the permeability of textile semi-finished products like woven or non-crimp fabrics have been examined. Especially, variations of textile architecture (stitch-bonding parameters for non-crimp fabrics [13][14][15][16][17] and weaving patterns as well as roving/fiber type for woven fabrics, preforming-related parameters like draping and shearing, [18][19][20][21][22][23] sewing [24][25][26] and binder application [27][28][29] can have a large impact on in-plane as well as out-of-plane permeability. Studies have shown that textiles with nearly identical mechanical properties can exhibit strongly varying permeability values up to the point where the injection time varies by a factor of 200.…”
Section: Test Planmentioning
confidence: 99%
“…During numerous research works, influences on the permeability of textile semi-finished products like woven or non-crimp fabrics have been examined. Especially, variations of textile architecture (stitch-bonding parameters for non-crimp fabrics [13][14][15][16][17] and weaving patterns as well as roving/fiber type for woven fabrics, preforming-related parameters like draping and shearing, [18][19][20][21][22][23] sewing [24][25][26] and binder application [27][28][29] can have a large impact on in-plane as well as out-of-plane permeability. Studies have shown that textiles with nearly identical mechanical properties can exhibit strongly varying permeability values up to the point where the injection time varies by a factor of 200.…”
Section: Test Planmentioning
confidence: 99%
“…Compared to electric sensors, they have several advantages: they are not disturbed by electromagnetic waves (e.g., radio waves, background radiation), therefore they do not need electromagnetic shielding, and optical fibers does not produce electromagnetic interference, either [ 7 , 8 ]. Their material is highly corrosion-resistant and can withstand high temperatures, therefore the sensor can be used for monitoring the manufacturing process [ 9 , 10 ] and structural health monitoring of composites [ 11 ] or even civil structures [ 12 ]. The sensors can be easily installed due to their small size, small mass, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating optical fibers during carbon fibre based preform fabrication itself is promising and has been reported earlier [ 24 ]. In this method optical fibers were stitched into each fiber preform along the middle plane of the laminate.…”
Section: Composite Materials With Embedded Fiber Sensors: Fabricatmentioning
confidence: 99%